2011
DOI: 10.7202/045609ar
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Newcomers to Fransaskois Schools: Opportunities for community collaboration

Abstract: Ce document est protégé par la loi sur le droit d'auteur. L'utilisation des services d'Érudit (y compris la reproduction) est assujettie à sa politique d'utilisation que vous pouvez consulter en ligne.https://apropos.erudit.org/fr/usagers/politique-dutilisation/ Cet article est diffusé et préservé par Érudit.Érudit est un consortium interuniversitaire sans but lucratif composé de l'Université de Montréal, l'Université Laval et l'Université du Québec à Montréal. Il a pour mission la promotion et la valorisation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…A review of the research revealed that some studies specifically focused on francophone newcomers (L. Carlson Berg, 2011; L. D. Carlson Berg, 2010; Jacquet et al, 2008; Liboy & Patouma, 2021).…”
Section: Literature Review Processmentioning
confidence: 99%
See 3 more Smart Citations
“…A review of the research revealed that some studies specifically focused on francophone newcomers (L. Carlson Berg, 2011; L. D. Carlson Berg, 2010; Jacquet et al, 2008; Liboy & Patouma, 2021).…”
Section: Literature Review Processmentioning
confidence: 99%
“…Immigrants with traumatic backgrounds are particularly affected by this, as they experience interruptions to their schooling (Benimmas et al, 2017). For instance, immigrant students and parents in one Saskatchewan French school considered the differences in pre- and post-migration educational environments as major barriers to integration (L. D. Carlson Berg, 2010).…”
Section: School Integration Experiencesmentioning
confidence: 99%
See 2 more Smart Citations
“…Canadians have not always embraced demographic change and increasing ethnocultural diversity (Lund, 2006a(Lund, , 2006bPreibisch, 2004). Often characterized internationally as a kind and caring nation, Canada's deep, dark past has dominated recent academic and public discourse with respect to the historical and contemporary mistreatment and marginalization of its Indigenous population/citizens (Battiste, 2013;Daschuk, 2013;King, 2013). Further, new immigrants, refugees, temporary foreign workers, as well as non-white and Indigenous Canadians continue to face perpetual, and blatant institutional racism and marginalization throughout Canadian society (Ibrahim, 2021;Perkel, 2018).…”
Section: Rurality and Resistance Toward Newcomersmentioning
confidence: 99%